2022
DOI: 10.1016/j.radi.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The use of deep learning towards dose optimization in low-dose computed tomography: A scoping review

Abstract: Introduction: Low-dose computed tomography tends to produce lower image quality than normal dose computed tomography (CT) although it can help to reduce radiation hazards of CT scanning. Research has shown that Artificial Intelligence (AI) technologies, especially deep learning can help enhance the image quality of low-dose CT by denoising images. This scoping review aims to create an overview on how AI technologies, especially deep learning, can be used in dose optimisation for low-dose CT. Methods: Literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…It has been shown that the CT value of pulmonary lesions in NP was lower than that in non-NP and may help predict NP early [ 95 ]. In order to reduce radiation damage, recent studies tried to adopt a machine-learning radiomics model based on radiographic features observed on non-enhanced CT scans or low-dose CT scans to recognize pulmonary consolidation in the early stage of NP in children [ 96 , 97 ]. Moreover, studies have found that lower kV combined with high Iterative Reconstruction in the CT pulmonary angiogram can maintain image quality [ 98 , 99 ].…”
Section: Prediction and Early Recognitionmentioning
confidence: 99%
“…It has been shown that the CT value of pulmonary lesions in NP was lower than that in non-NP and may help predict NP early [ 95 ]. In order to reduce radiation damage, recent studies tried to adopt a machine-learning radiomics model based on radiographic features observed on non-enhanced CT scans or low-dose CT scans to recognize pulmonary consolidation in the early stage of NP in children [ 96 , 97 ]. Moreover, studies have found that lower kV combined with high Iterative Reconstruction in the CT pulmonary angiogram can maintain image quality [ 98 , 99 ].…”
Section: Prediction and Early Recognitionmentioning
confidence: 99%
“…As a result, to solve this issue, a machine learning framework was developed that allowed for reconstructing image parameters and denoising the quality of the image when low radiation was used. This resulted in improved image quality to equate to the regular-dose CT image quality, thus allowing patients to be exposed to less radiation while still obtaining a diagnostic result [ 30 ].…”
Section: Ai: Cardiology Imaging Applicationsmentioning
confidence: 99%
“…4 Usually, by changing the scanning parameters such as tube current, pitch, tube potential/voltage and rotation/exposure time, CT dose reduction can be achieved significantly. While, this may lead to compromised CT image quality in terms of spatial/density contrast and resolution, and may introduce noise and artifacts, 5 which can be reflected by image quality evaluation metrics. 6 Therefore, how to improve the quality of LDCT is of great significance for early disease screening in clinical practice.…”
Section: Introductionmentioning
confidence: 99%